Soziale Arbeit im Schweizer Justizvollzug – Forschung im Kontext einer Fachhochschule - Isenhardt, Anna; Marti, Irene; Pruin, Ineke; Richter, Marina; Weber, Jonas (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
Based on many years of experience and engagement with the Swiss prison system, this article examines the role and development of social work in this field. The focus is on different institutional models, regional differences, and the question of how social work professionals position themselves in a tense environment between helping and controlling. Experience from various research projects shows that social work in the prison system is not only well established today, but also plays a key role in shaping a resource-oriented and humane prison system. (machine translation)